1995
DOI: 10.1016/0147-9571(95)98850-h
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of group A and group B rotaviruses in the feces of neonatal dairy calves from California

Abstract: 136 fecal samples, collected from 47 dairy calves on a calf ranch and in a dairy herd in California, were tested for the presence of group A and group B rotaviruses by reverse transcription-polymerase chain reaction (RT-PCR). Samples were collected from each calf at days 1, 7 and 14. Within the 14 day period, 44 calves (94%) were positive for group A rotavirus and an unexpectedly high number of calves (38 calves, 81%) were positive for group B rotavirus. When these samples were examined by polyacrylamide gel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…These samples might possibly represent group A bovine rotaviruses with an unusual genome segment 6 sequence that was possibly not amplified by partial length VP6 specific primers. Similar findings were reported by Chinsangaram et al[1] in a study where out of 47 PAGE positive samples, three samples were found negative for group A rotavirus by RT-PCR which were thought to contain unusual genome segment 6 sequence. In a study by Rodriguez-Limas et al[13], group A rotavirus has been found in 10% (12/128) of screened samples from dairy and beef calves with an immunocard that detected group A rotavirus VP6 gene.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…These samples might possibly represent group A bovine rotaviruses with an unusual genome segment 6 sequence that was possibly not amplified by partial length VP6 specific primers. Similar findings were reported by Chinsangaram et al[1] in a study where out of 47 PAGE positive samples, three samples were found negative for group A rotavirus by RT-PCR which were thought to contain unusual genome segment 6 sequence. In a study by Rodriguez-Limas et al[13], group A rotavirus has been found in 10% (12/128) of screened samples from dairy and beef calves with an immunocard that detected group A rotavirus VP6 gene.…”
supporting
confidence: 86%
“…In a study by Rodriguez-Limas et al[13], group A rotavirus has been found in 10% (12/128) of screened samples from dairy and beef calves with an immunocard that detected group A rotavirus VP6 gene. In another study by Theil et al[19] group A rotavirus has been found in 22% of diarrhoeic calves from dairy and beef herds by cell culture immunofluorescence assay and Chinsangaram et al[1] detected group A rotavirus from 94% (44/47) calves, directly by RT-PCR in faecal samples. The present study confirms the circulation of group A rotavirus in the region and further studies are required to characterize the genotypes prevalent and their zoonotic implications.…”
mentioning
confidence: 96%
“…114,115 Antibodies to rotavirus can be found in more than 90% of unvaccinated cattle, 116 and the virus was isolated from 94% of dairy calves at a large dairy and calf ranch during the first 2 weeks of life. 117 It has also been isolated from approximately 20% of calf diarrhea samples, 118,119 and from at least one calf on 63% of farms. 120 Calves become infected after ingesting the virus from fecal contamination of the environment, because the virus remains quite stable if the temperature does not get near freezing.…”
Section: Rotavirusmentioning
confidence: 99%
“…In weaned heifers, another important endemic disease is infectious bovine keratoconjunctivitis (IBK, or pinkeye), caused by Moraxella bovis [38]. With the exception of BVDV, some Salmonella species, some mycoplasmal species, and some specific strains of E coli, the pathogens responsible for most calfhood disease are ubiquitous and are present in a proportion of apparently healthy cattle on most dairy operations [39][40][41][42][43][44][45].…”
Section: Hazard Identificationmentioning
confidence: 99%